PROSES PELAKSANAAN PROGRAM PENGEMBANGAN USAHA AGRIBISNIS PERDESAAN DI KECAMATAN LEDO KABUPATEN BENGKAYANG - Eko Hadiprasojo E.01108136 (FISIP Universitas Tanjungpura, 2013)
The title of this article is the implementation of Rural Agribusiness Development Program in District Ledo Bengkayang. The purpose of writing this article is to describe the process Implemenetasi Rural Agribusiness Development Program in the District of Ledo and factors that influence it. The method used in this paper is a qualitative method. The results obtained from this study is, that the process of implementation of Rural Agribusiness Development Program in District Ledo Bengkayang are in accordance with the applicable provisions. But the substance of the program have not been able to achieve the desired goals and objectives are to improve the lives of farmers who are members of the Association of Farmers Group. Joint Farmers have not been able to take advantage of venture capital assistance to improve the downstream sub-sector of agribusiness and agri-support sub-system, so efforts to reduce poverty in Sub Ledo will not materialize. It is influenced by several factors, namely, inter-organizational communication factors, resources, and the disposition of the implementor. Hence the need for education about the program PUAP especially in developing joint business plans.Keywords: Rural Agribusiness, Downstream Agrebisnis, Sub Agrebisnis System Support.